2021
DOI: 10.1007/s40122-021-00328-y
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Gender Difference in the Response to onabotulinumtoxinA in Chronic Migraine? Insights from a Real-Life European Multicenter Study on 2879 Patients

Abstract: Introduction: Migraine is mostly a female disorder because of its lower prevalence in men.Less than 20% of patients included in the available studies on migraine treatments are men; hence, the evidence on migraine treatments might not apply to men. The aims of the present study were to provide reliable information on the effectiveness of onabotulinumtox-inA (BT-A) for chronic migraine in men and to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…The gender difference in BT-A response has been studied, but with conflicting results. In particular, a previous study failed to find a clear gender difference in the clinical response towards BT-A [ 27 ]. Despite its statistical significance, sex difference in the response towards BT-A is gravated by the great difference between men and women numerosity as well as a higher number of drop-outs among men; thus, the exact magnitude of this difference is difficultly detectable but, at least, questionable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender difference in BT-A response has been studied, but with conflicting results. In particular, a previous study failed to find a clear gender difference in the clinical response towards BT-A [ 27 ]. Despite its statistical significance, sex difference in the response towards BT-A is gravated by the great difference between men and women numerosity as well as a higher number of drop-outs among men; thus, the exact magnitude of this difference is difficultly detectable but, at least, questionable.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of this study have been previously published, since two more articles were derived from the analysis of the present dataset [ 26 , 27 ]; this is a pooled patient-level analysis of data from real-life studies on patients with CM treated with BT-A at 16 European headache centers. The centers potentially participating in the study were first identified through a MEDLINE search of the most recent publications on BT-A treatment for CM in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…Several real-world studies have been published, with findings consistent with PREEMPT studies in CM patients with and without MOH [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. Real-world studies primarily exploring the effectiveness and safety of BT-A compared to the baseline are summarized in Table 2 .…”
Section: Clinical Use Of Bt-a In the Treatment Of Chronic Migrainementioning
confidence: 99%
“…Firstly, this group determined that two BT-A cycles are usually enough to establish if a patient is a responder or a non-responder to the BT-A. Indeed, patients who do not respond to the first two cycles of BT-A are unlikely to respond to the third cycle [ 125 ]. This indicates that, as BT-A effects spread rapidly, the first 6 months of treatment should be enough to establish if BT-A should be continued or not.…”
Section: Clinical Use Of Bt-a In the Treatment Of Chronic Migrainementioning
confidence: 99%
See 1 more Smart Citation